2004
DOI: 10.1590/s0102-311x2004000600015
|View full text |Cite
|
Sign up to set email alerts
|

O perfil do idoso de baixa renda no Município de São Carlos, São Paulo, Brasil: um estudo epidemiológico

Abstract: This study focuses on the health profile of the elderly population in São Carlos, São Paulo State, Brazil, in 2003

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
20
5
80

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(115 citation statements)
references
References 18 publications
7
20
5
80
Order By: Relevance
“…Most elderly men were married or lived with a partner, which diff ered from a study conducted in Australia, China, Britain, Greece and Italy (76.8%) (13) , in which the percentages were higher. In Brazil, a survey conducted in São Carlos-SP (75.4%) (14) converged with this inves ga on. Being married or living with a partner enables healthcare professionals to involve the family in care for this popula on group, contribu ng to the s mula on of elderly men in health care.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Most elderly men were married or lived with a partner, which diff ered from a study conducted in Australia, China, Britain, Greece and Italy (76.8%) (13) , in which the percentages were higher. In Brazil, a survey conducted in São Carlos-SP (75.4%) (14) converged with this inves ga on. Being married or living with a partner enables healthcare professionals to involve the family in care for this popula on group, contribu ng to the s mula on of elderly men in health care.…”
Section: Discussionsupporting
confidence: 64%
“…A survey conducted in São Paulo found that elderly men had fewer morbidi es (1 to 5) than what was found in the data obtained in this study (14) . Hypertension (73.2%) and vision problems (67.1%), although in diff erent percentages, were also more prevalent in another study (16) .…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…12 In addition, there are higher rates of mortality from external causes, such as violence, among men especially as young adults. 4 In our study, the risk of institutionalization increased with increasing age. The risk of functional disability doubles with each successive decade of life, 8 with a higher prevalence of chronic diseases and hospital admissions among the oldest adults.…”
Section: Discussionsupporting
confidence: 50%
“…In contrast, improving literacy may result in greater responsiveness of the elderly to health promotion programs. 4 One of the major contributors to functional decline in the elderly is physical inactivity. 22 In our study, lower levels of physical activity and functional capacity were associated with institutionalization.…”
Section: Discussionmentioning
confidence: 99%